2013
DOI: 10.33899/csmj.2013.163548
|View full text |Cite
|
Sign up to set email alerts
|

Nullity and Bounds to the Nullity of Dendrimer Graphs

Abstract: In this paper, a high zero-sum weighting is applied to evaluate the nullity of a dendrimer graph for some special graphs such as cycles, paths, complete graphs, complete bipartite graphs and star graphs.Finally, we introduce and prove a sharp lower and a sharp upper bound for the nullity of the coalescence graph of two graphs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In [18], [19], Sciriha determined properties of substructures responsible for a graph to be singular, establishing that in a graph of nullity η, there are η induced subgraphs (termed singular configurations) of nullity one from a prescribed list. In [22], Sharaf and Ali proceeded to determine a sharp lower bound and a sharp upper bound for the nullity of the coalescence of two graphs. They showed that the nullity of the coalescence of s component graphs varies by at most s − 1 from the sum of the nullities of the component graphs.…”
Section: Proposition 15 ([16])mentioning
confidence: 99%
“…In [18], [19], Sciriha determined properties of substructures responsible for a graph to be singular, establishing that in a graph of nullity η, there are η induced subgraphs (termed singular configurations) of nullity one from a prescribed list. In [22], Sharaf and Ali proceeded to determine a sharp lower bound and a sharp upper bound for the nullity of the coalescence of two graphs. They showed that the nullity of the coalescence of s component graphs varies by at most s − 1 from the sum of the nullities of the component graphs.…”
Section: Proposition 15 ([16])mentioning
confidence: 99%
“…A non-trivial vertex weighting of a graph G is called a zero sum weighting provided that for each v∈V (G), u∈N(v)f(u) = 0, that is the summation is taken over all u∈N(v), See (Brown et al, 1993). Out of all zero-sum weightings of a graph G, a high zero sum weighting (hzsw) of G, is one that uses a maximum number of non-zero independent variables, see (Sharaf & Ali, 2013). The nullity, η(G of a graph G) is the multiplicity of zero as an eigenvalue of its adjacency matrix, see (Cheng & Liu, 2007)., So a graph is singular if its nullity is at least one.…”
Section: Introductionmentioning
confidence: 99%
“…The nullity of most known graphs can be easily determined using the hzsw tool, since number of independent variables used in a hzsw of the graph is exactly η(G). Thus, η(Kn)=0, for n≥2, η(Km,n)=m +n-2, η(Pn)=1 if n is odd and zero where n is even, η(Cn)=2 if n=0 mod4 and it is non-singular otherwise, see (Cheng, & Liu, 2007) and (Sharaf & Ali, 2013). Maximum nullity of graphs was studied in (Gutman & Sciriha, 1996).…”
Section: Introductionmentioning
confidence: 99%